2006
DOI: 10.1109/iecon.2006.347910
|View full text |Cite
|
Sign up to set email alerts
|

Sensorless Control of a PMSM Synchronous Motor at Low Speed

Abstract: This paper presents a self-sensing technique for a surface-mounted permanent-magnet synchronous machine (SM-PMSM) based on high frequency voltage injection. The reactances of the high frequency model vary as a function of rotor position and a simple method based on measured currents and voltages can be used to identify those reactances. Using the motor reactances, the rotor position and velocity are determined. The proposed technique is relatively independent of the machine parameters and it can be applied to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Arias et al [136] studied the impact of the speed in the FOC structure and proposed an adaptive control algorithm to extend the speed operation. Miranda et al [137] showed a self-sensor technique for an SM-PMSM with high-frequency voltage injection, with which the rotor position and velocity can be determined. Monteiro et al [138] proposed a method to reduce electromagnetic torque ripple and copper losses in an SM-PMSM and showed that their proposal can improve the performance of this kind of machine.…”
Section: Permanent Magnet Synchronous Motor (Pmsm)mentioning
confidence: 99%
See 1 more Smart Citation
“…Arias et al [136] studied the impact of the speed in the FOC structure and proposed an adaptive control algorithm to extend the speed operation. Miranda et al [137] showed a self-sensor technique for an SM-PMSM with high-frequency voltage injection, with which the rotor position and velocity can be determined. Monteiro et al [138] proposed a method to reduce electromagnetic torque ripple and copper losses in an SM-PMSM and showed that their proposal can improve the performance of this kind of machine.…”
Section: Permanent Magnet Synchronous Motor (Pmsm)mentioning
confidence: 99%
“…The main disadvantages of the PMSM are its high cost and the demagnetization of permanent magnet materials in harsh environments, such as high temperature and vibration. In addition, the lack of rare earth permanent magnet materials, particularly in regions without abundant rare earth resources, is the biggest challenge to the use of PMSMs in propulsion systems for many countries [134][135][136][137].…”
Section: Permanent Magnet Synchronous Motor (Pmsm)mentioning
confidence: 99%
“…The authors have proposed a solution for extracting the rotor position information from measured voltages and currents that combines high frequency signal injection with system identification techniques [19]. In the proposed technique it was considered that all the information concerning the rotor position is fully embedded in the machine inductance.…”
Section: Introductionmentioning
confidence: 99%
“…Since estimated parameters are functions of the rotor position thus we can estimate rotor position from these parameters. From the identified parameter y-, y-and y-the parameters needed for estimated parameters vary with the rotor angle and thus one can estimate the rotor position from(19). From the estimated parameter 0 Or) the rotor angle position can…”
mentioning
confidence: 99%
“…By the corresponding stator current vector reaction it is possible to evaluate a complex reactance that depends on the rotor position, from which extracting the rotor position itself is possible. Other schemes utilize a sinusoidal source of test signal, superimposed to the fundamental excitation signal, either in the form of rotating voltage vector [7][8][9][10] or pulsating signal along the direction of a specific axis [11,12]. The proposed algorithm features a novel method of estimating the machine inductances.…”
Section: Introductionmentioning
confidence: 99%